Hyper‐reduced direct numerical simulation of voids in welded joints via image‐based modeling. (11th February 2020) - Lacourt, Laurent; Ryckelynck, David; Forest, Samuel; de Rancourt, Victor; Flouriot, Sylvain
Summary: Defects such as gas pores can be formed and trapped in the fusion zone during laser welding. These defects can significantly affect the mechanical reliability of the welded joint. Current nondestructive inspection technologies are able to detect micro‐voids in a mass production context. Finite element analysis can therefore be used to assess the lifetime of an observed component via image‐based modeling. Unfortunately, running a simulation per component entails a huge and generally unaffordable computational cost. In addition, voids do not admit a parametric modeling. In this paper, a numerical method is proposed to study the impact of defects on the mechanical response of a welded joint. It is based on model order reduction techniques that decrease the computational cost of each simulation related to an image‐based modeling. To tackle the reduction of nonparametric defects, a multiscale construction of the reduced basis is proposed, although no scale separation is assumed when computing the mechanical response of the structure. Some empirical modes are representing the structure behavior and other empirical modes are related to the defect‐induced local fluctuations. They are then assembled to simulate a defective joint. Assets and limitations of the proposed method are explored through a simplified two‐dimensional (2D) problem. For the sake of reproducibility, this 2D problem is fully parametric. Finally, a realistic three‐dimensional (3D) industrial case is presented, where voids geometries have been measured via computed tomography. This 3D problem being nonparametric, fluctuation modes must be computed on the fly, once the computed tomography has been performed.